Development of new vocational training modules on sustainable buildings maintenance and refurbishment - Herrando, M. (2016)
This article presents the methodology and main results obtained in Spain within the FORMAR project, a European-funded project under the Leonardo Da Vinci scheme (Lifelong Learning Programme), whose main goal is to jointly develop training resources and modules to improve the skills on sustainability issues of buildings maintenance and refurbishment workers, in three different European countries: Spain, Portugal (Project Coordinator) and France. The Units of Short-term Training (UST) developed within this project are focused on the VET of carpenters, painters, bricklayers, building technicians and installers of solar panels, and a transversal unit containing basic concepts on sustainable construction and nearly Zero Energy Buildings (n-ZEB) is also developed. In parallel, clients’ guides for the aforementioned professionals are also implemented to improve the information provided to clients and owners in order to support the procurement decisions regarding building products and materials. Therefore, the project provides an opportunity to exchange experiences between organizations of these three European countries, as the UST will be developed simultaneously in each of them, exploring opportunities for training, guidance and exchange of experience. Even though the UST will have a common structure and contents, they will be slightly different in each country to adapt them to the different specific training needs and regulations of Spain, Portugal and France. This paper details, as a case study, the development process of the UST for carpenters and building technicians in Spain, including the analysis of needs and existing training materials, the main contents developed and the evaluation and testing process of the UST, which involves the active participation of several stakeholders of this sector as well as a classroom testing to obtain the students’ feedback.